PLACE MARKETING IN PLANNING SUSTAINABLE DEVELOPMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Research background: Municipalities, as part of the public sector, have to use various methods to achieve their goals, including the ones that are indispensable for successful entrepreneurship. Local authorities plan, manage and control events of public importance. These activities must be in line with national policies and accepted in their development documents. It is logical for municipalities to formulate and communicate their strategies and spatial development perspectives to the public. The improvement of a sustainable development strategy is especially important because the administrative-territorial reform was completed in 2021. After this latest reform, the boundaries of districts, management and distribution of funding were changed significantly. Today several towns and communities have developed their marketing strategies, and each municipality has public relations or development departments that take care of the image of the area.Purpose of the article: The aim of this study is to analyse the importance of local marketing in the current sustainable development strategies of individual districts. Tasks of the research are to describe the essence of local marketing, to study the peculiarities of strategic planning in local governments, to analyse the current sustainable development strategies of Cesis, Valmiera and Smiltene counties in connection with local marketing and to draw conclusions on the research results.Methods: The work uses a monographic research method, analysis of scientific literature, analysis of regulatory enactments, a logically constructive method - for the formation of judgments and analysis of results, a method of synthesis - to combine elements into a single system.Findings & Value added: As a result of the study, the importance and impact of place marketing on the regional planning process was identified.